PERBANDINGAN SISTEM HUKUM MAHKAMAH KONSTITUSI INDONESIA DAN THAILAND - Misri, Fauzan Raisal; Gultom, Elfrida Ratnawati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research aims to analyze the comparison of the constitutional court legal systems in Indonesia and Thailand. This research uses a type of normative research using a historical approach and the legal materials used are primary and secondary legal materials consisting of statutory regulations, legal journals and the views of experts. The method used in drawing conclusions is the deductive technique of describing something from general things to specific or more specific things. The data obtained from this research is that the Constitutions of Indonesia and Thailand have differences and similarities. This difference can be seen from the aspects of independence and the judge selection process, judicial access to the Constitutional Court, as well as interpretive techniques. Meanwhile, the similarities include that they both have the function of guarding the constitution and have a high position of judicial authority. Differences in the legal system of the Constitutional Court can be caused by historical, cultural factors and the government system.Keywords: Analysis, Comparison, Constitutional Court, Indonesia, Thailand